2005
DOI: 10.1590/s0103-84782005000300008
|View full text |Cite
|
Sign up to set email alerts
|

Época de colheita e período de repouso dos frutos de mamão (Carica papaya L.) cv Golden na qualidade fisiológica das sementes

Abstract: RESUMO Este trabalho teve como objetivo verificar a influência da época de colheita e do período de repouso dos frutos na qualidade fisiológica de sementes de mamão. Os frutos, produzidos no inverno e no verão, da cv Golden (0, 2, 4, 6, 8, 10 and 12 days) and after storage of the seeds for 30 days at 15ºC. The experimental design used was a completely randomized arrangement in 2x7x2 factorial scheme with four replications. The treatments of the factorial consisted of the combination of two fruit harvest times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 7 publications
0
7
1
11
Order By: Relevance
“…The potential for seed germination was not increased with the fungicide treatment and the storage, contradicting the conclusions of Aroucha et al (2005), who found that the storage of papaya seeds for 30 days increased the percentage of germination.…”
Section: Seed Qualitycontrasting
confidence: 66%
“…The potential for seed germination was not increased with the fungicide treatment and the storage, contradicting the conclusions of Aroucha et al (2005), who found that the storage of papaya seeds for 30 days increased the percentage of germination.…”
Section: Seed Qualitycontrasting
confidence: 66%
“…Their exact function is still unknown, but studies have shown that they are related to the protection of cellular or molecular structures from damage, which may result from water loss during the desiccation of the seed (Goyal et al 2005). Aroucha et al (2005), working with papaya seeds of the Golden and Taining 01 cultivars, found that recently collected seeds, regardless of the state of maturation of the fruits, displayed low initial germination, making the storage period necessary for seed germination.…”
Section: Induction Of Embryogenic Culturesmentioning
confidence: 99%
“…Além disso, é maior a probabilidade de se obter lotes pouco homogêneos quanto à qualidade, quando a secagem é realizada sem que haja controle efetivo das variáveis envolvidas no processo. Quando a secagem não é realizada ao sol ou à sombra, empregam-se estufas com circulação forçada do ar, em que o único parâmetro controlado é a temperatura (Viggiano et al, 2000b;Aroucha et al, 2005;Tokuhisa et al, 2007).…”
Section: Introductionunclassified